Rhythms of Core Clock Genes and Spontaneous Locomotor Activity in Post-Status Epilepticus Model of Mesial Temporal Lobe Epilepsy - Matos, Heloisa de Carvalho; Koike, Bruna Del Vechio; Pereira, Wanessa dos Santos; de Andrade, Tiago G.; Castro, Olagide W.; Duzzioni, Marcelo; Kodali, Maheedhar; Leite, Joao P.; Shetty, Ashok K.; Gitaí, Daniel L. G. (Frontiers in Neurology, 2018)
The interaction of Mesial Temporal Lobe Epilepsy (mTLE) with the circadian system control is apparent from an oscillatory pattern of limbic seizures, daytime’s effect on seizure onset and the efficacy of antiepileptic drugs. Moreover, seizures per se can interfere with the biological rhythm output, including circadian oscillation of body temperature, locomotor activity, EEG pattern as well as the transcriptome. However, the molecular mechanisms underlying this cross-talk remain unclear. In this study, we systematically evaluated the temporal expression of seven core circadian transcripts (Bmal1, Clock, Cry1, Cry2, Per1, Per2, and Per3) and the spontaneous locomotor activity (SLA) in post-status epilepticus (SE) model of mTLE. Twenty-four hour oscillating spontaneous locomotor activity (SLA) remained intact in post-SE groups although the circadian phase and the amount and intensity of activity were changed in early post-SE and epileptic phases. The acrophase of the SLA rhythm was delayed during epileptogenesis, a fragmented 24h rhythmicity and extended active phase length appeared in the epileptic phase. The temporal expression of circadian transcripts Bmal1, Cry1, Cry2, Per1, Per2, and Per3 was also substantially altered. The oscillatory expression of Bmal1 was maintained in rats imperiled to SE, but with lower amplitude (A= 0.2) and an advanced acrophase in the epileptic phase. The diurnal rhythm of Cry1 and Cry2 was absent in the early post-SE but was recovered in the epileptic phase. Per1 and Per2 rhythmic expression were disrupted in post-SE groups while Per3 presented an arrhythmic profile in the epileptic phase, only. The expression of Clock did not display rhythmic pattern in any condition. These oscillating patterns of core clock genes may contribute to hippocampal 24-hour cycling and, consequently to seizure periodicity. Furthermore, by using a pool of samples collected at 6 different Zeitgeber Times (ZT), we found that all clock transcripts were significantly dysregulated after SE induction, except Per3 and Per2. Collectively, altered SLA rhythm in early post-SE and epileptic phases implies a possible role for seizure as a nonphotic cue, which is likely linked to activation of hippocampal–accumbens pathway. On the other hand, altered temporal expression of the clock genes after SE suggests their involvement in the MTLE.